PERFORMANCE ASSESSMENT OF THE FINANCIAL SECTOR IN THE HEALTH INDUSTRY ON THE INDONESIA STOCK EXCHANGE BEFORE AND DURING THE PANDEMIC - Ai Tanahashi; Rini Tri Hastuti (Graduate Program of Universitas Tarumanagara, 2024)
The effect following the Corona virus pandemic on the global economy was very large with the International Monetary Fund estimating a contraction of the global economy of 4.4% in 2020 which would result in a very large recession after the second world war. With this continuation, Indonesia's economic growth contracted by 2.07% in 2020 and is expected to improve gradually in 2021. The level of profitability can be determined by analyzing financial reports which are defined as a means of systematically conveying financial position and performance which is composed of a corporate whose aim is to receive notifications in the form of useful information for stakeholders to make decisions related to the economy. The purpose of this research is to determine the financial performance analysis before and during the Corona virus pandemic in healthcare companies listed on the Indonesia Stock Exchange from 2018 to 2021. The method used in this research is purposive sampling, and with this method, 17 companies that meet the specified criteria were identified. As a result, 68 data points were obtained as the research sample. Then, this study employs the paired sample t-test method to analyze the data. The research findings indicate differences in profitability and activity before and during the Corona virus pandemic, while liquidity and leverage remain unchanged.